2019
DOI: 10.1111/cyt.12650
|View full text |Cite
|
Sign up to set email alerts
|

Cytological features of dyshormonogenetic goitre: A diagnostic pitfall

Abstract: Dyshormonogenetic goitre, being rare, infrequently reaches the cytopathologist's desk. This letter reports a case of a child with dyshormonogenetic goitre, highlighting its cytological features and common differential diagnoses.Dyshormonogenetic goitre (DG) is a rare cause of congenital hypothyroidism, resulting from a lack of enzymes necessary for biosynthesis/transport of thyroid hormones. The disease usually presents in childhood with symptoms secondary to hypothyroidism.Rarely, patients may be euthyroid. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…6 The underlying cause of the inborn metabolic error is a defect in thyroid hormone synthesis that may be because of defects in Only four case reports have described the cytological findings of dyshormonogenetic goiter. [2][3][4][5][6] By comparing the cytomorphological features of these cases and this case, we observed that the majority (83.3%) showed syncytial and microfollicular arrangement of follicular epithelial cells, nucleomegaly and nuclear hypochromasia. Half of the cases noted empty follicles, nuclear overlap/crowding, and colloid.…”
Section: Case Reportmentioning
confidence: 75%
See 1 more Smart Citation
“…6 The underlying cause of the inborn metabolic error is a defect in thyroid hormone synthesis that may be because of defects in Only four case reports have described the cytological findings of dyshormonogenetic goiter. [2][3][4][5][6] By comparing the cytomorphological features of these cases and this case, we observed that the majority (83.3%) showed syncytial and microfollicular arrangement of follicular epithelial cells, nucleomegaly and nuclear hypochromasia. Half of the cases noted empty follicles, nuclear overlap/crowding, and colloid.…”
Section: Case Reportmentioning
confidence: 75%
“…However, cytological features were reported in only four case reports of dyshormonogenetic goiter. [2][3][4][5] We present a case of dyshormonogenetic goiter in a 9-yearold girl. We compared our case with other similar case reports in the literature to elaborate on the cytomorphological features of this benign entity.…”
Section: Introductionmentioning
confidence: 99%
“…Adequate cytological diagnosis in nodules of patients with dyshormonogenesis might be demanding as a result of specific architectural and cytological appearances that may lead to an erroneous interpretation of the malignancy. The main findings are summarized in Table 2 (Matos et al 1994, Mahajan et al 2019. The cytological approach needs much refinement, encompassing the discernment of many conditions, such as hyperplastic nodule, post-radioiodine changes, follicular neoplasm, and non-invasive follicular thyroid neoplasm with papillary-like nuclear features (Matos et al 1994, Mahajan et al 2019.…”
Section: Thyroid Cancer Diagnostic Pitfalls In Patients With Congenital Hypothyroidism With Nodular Goitermentioning
confidence: 99%
“…The main findings are summarized in Table 2 (Matos et al 1994, Mahajan et al 2019. The cytological approach needs much refinement, encompassing the discernment of many conditions, such as hyperplastic nodule, post-radioiodine changes, follicular neoplasm, and non-invasive follicular thyroid neoplasm with papillary-like nuclear features (Matos et al 1994, Mahajan et al 2019. There may also be foci of papillary hyperplasia and mitotic activity, which could again lead to overdiagnosis of DTC.…”
Section: Thyroid Cancer Diagnostic Pitfalls In Patients With Congenital Hypothyroidism With Nodular Goitermentioning
confidence: 99%
See 1 more Smart Citation